Internet Addiction and Its Relationship to Gender, Depression and Anxiety Among Medical Students in Anbar Governorate-West of Iraq. - Al Shawi, Ameel F; Hameed, Aseel K; Shalal, Aatika I; Abd Kareem, Sara S; Majeed, Mujtabaa A; Humidy, Sara T (Community Health Equity Research & Policy, 2022)
Introduction: The rapid increase of internet using was associated with a rise in internet addiction (IA) especially among adolescent and young adults that may associated with underlying psychological disorders. The aims of the study: a) to estimate the prevalence of internet addiction among medical students in Anbar governorate, b) to assess the effect of internet addiction on mental health by measuring the association of IA with depression and anxiety among the students. Methods: A cross sectional study was carried out during the period from February to April 2019. A self-administered questionnaire was used which consisted from demographic questions, the Young Internet Addiction test to evaluate the internet addiction among the subjects and the Depression Anxiety stress scales (DASS) for assessing the depression and anxiety symptoms among the medical students. Results: 47.5% of the subjects had mild internet addiction, proportion of moderate addiction among the participants was 23%. There was a significant association between internet addiction with depression and anxiety. The subjects with internet addiction had OR = 2.302 for depression development (P < 0.001), also the students with internet addiction had OR= 3.088 for anxiety development (p < 0.001). Conclusion: High rate of internet addiction among medical students in Anbar city- west of Iraq and there was significant association between internet addition and mental disorders of the subjects.